International Law in Search of Rebalance - Vicuña, Francisco Orrego (International Law E-Books Online, Collection 2025., 2025)
Is the nature of international law today essentially different from the past five centuries, or does it reflect a gradual transformation within certain basic principles that remain unaltered? This book considers the profound structural changes of international law, in line with the requirements of globalization, and tracks the law's evolution over the centuries with special regard to the dichotomy between idealism and pragmatism. International law was the vocation and passion of Francisco Orrego Vicuña, who dedicated his life to the observation, study, teaching and practice of this important legal discipline. He was a privileged witness of the great advances and changes that international law has undergone in the last 50 years, and this book - with an Introduction by Rüdiger Wolfrum and Michael Wood and the assistance of Simon C. Milnes - is the result of years of work and research. It is, posthumously, his magnum opus.